Physical activity, sedentary time, TV viewing, physical fitness and cardiovascular disease risk in adolescents: The HELENA study. (1st March 2018) - Barker, Alan R.; Gracia-Marco, Luis; Ruiz, Jonatan R.; Castillo, Manuel J.; Aparicio-Ugarriza, Raquel; González-Gross, Marcela; Kafatos, Anthony; Androutsos, Odysseas; Polito, Angela; Molnar, Dénes; Widhalm, Kurt; Moreno, Luis A.
Abstract: Background: To examine the independent associations between physical activity (PA) intensities, sedentary time (ST), TV viewing, cardiorespiratory fitness (CRF) and muscular fitness (MF) with cardiovascular disease (CVD) risk in youth. Methods: A cross-sectional study on 534 European adolescents (252 males, 282 females, 12.5–17.5 years). Minutes per day of light (LPA), moderate (MPA) and vigorous (VPA) PA and total ST were measured using accelerometers. TV viewing time was measured using a questionnaire. CRF and MF were measured using the 20 m shuttle run test and a hand dynamometer respectively. CVD outcomes included markers of body composition (body mass index (BMI), waist circumference (WC), WC/height (Ht) and sum of skinfolds (SumSF)), blood pressure, blood lipids and insulin resistance (HOMA-IR). Clustered CVD risk was calculated using SumSF, HOMA-IR, blood lipids and blood pressure. Results: LPA had a significant positive independent relationship with all body composition outcomes ( P   <  0.001) and clustered CVD risk ( P   =  0.046). VPA was negatively related to SumSF ( P   <  0.001), BMI ( P   =  0.018), WC/Ht ( P   =  0.013) and clustered CVD risk ( P   =  0.001), but was non-significant for all when other exposures were considered ( P   >  0.10). MPA had a negative independent relationship with only WC ( P   =  0.029) and ST was not significantly related to CVD risk ( P   >  0.16). TV viewing had a significant positive independent relationship with HOMA-IR ( P   <  0.001) and clustered CVD risk ( P   =  0.019). CRF (all P   <  0.002) and MF (all P   <  0.009) had a negative independent relationship with body composition outcomes and clustered CVD risk. Conclusions: Public health guidelines should prioritize on increasing levels of CRF, MF and VPA, and reducing TV viewing time to lower CVD risk in youth.